(3Cda HGAs - (3CHh GdMLGL GdHdhj , jhSa Hf eMeO Hf YHO Gddg Hf jMji Hf ZGdH,J (B604 (3g` s
(3ChdgG (B:s
(3CeG HYO(B: (3aEfj YReJ Ydi Cf CLeY gj gPg GdChQGb cd eYfi Qb Ch QGb, eeG gh YfOj eSJMSf dG eSJNTf heSJedM dG eSJbHM, hCKHJ ajg ef GdahGFO eG jRQj Ydi GdaQGFO s
(3BNQgG (B:s
(3eG CedM GdYde EPG cfJ aj Vjb JQGg Yfc bO aQLG hef jcf hGSY Yde eJi ojrNWi jLO ef bhdg eNQLG Je GdLRA GdChd ef cJGH GdCdHGA aj GdCda HGA, jJdhg GdLRA GdKGfj HGH GdCda eY GdOGd s
(3ef fSNI CNQis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B247 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B330s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B56 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B17) s
Keywords: (3GdCOHs